Peripheral Lymphadenopathy in Children: Cytomorphological Spectrum and Interesting Diagnoses - Arti KHATRI; Nidhi MAHAJAN; Sonali MALIK; Kanika RASTOGI; Parveen KUMAR; Diganta SAIKIA (Federation of Turkish Pathology Societies, 2021)
Objective: Peripheral lymphadenopathy is a common complaint in the pediatric outpatient department. Fine needle aspiration cytology is the first investigation of choice with a high sensitivity for diagnosis but cytology may be challenging in some cases. The study was planned to study the cytomorphological spectrum and discuss a few interesting cases. Material and Method: 1890 paediatric subjects' up to 12 years of age with significant peripheral lymph node enlargement and an adequate cytology specimen were included in the study. Inadequate aspirates were excluded. Results: The majority of children presented within 4-8 years of age with a male to female ratio of 1.7:1. The anterior cervical group was most commonly affected, followed by the posterior cervical, axillary and inguinal. Reactive lymphadenitis constituted the majority of the diagnoses, followed by Tuberculosis, acute suppurative, BCG-induced lymphadenitis, Kimura disease, Rosai-Dorfmann disease and Kikuchi-Fujimoto disease. Lymphomas and metastatic malignancies were less common, and mainly consisted of Hodgkin lymphoma, non-Hodgkin lymphoma, anaplastic large cell lymphoma, and Langerhans cell histiocytosis. Cytomorphological features of a few challenging and interesting cases have been discussed. Conclusion: Non neoplastic causes of lymphadenopathy predominate in the pediatric age group. A definitive diagnosis rests upon a complete clinical, radiological, microbiological, and cyto-histopathological correlation with the use of ancillary techniques wherever necessary.